The Prodigal Son: Does the Younger Brother Always Care for His Parents in Old Age? - Mizuki Komura; Hikaru Ogawa (Institute for the Study of Labor (IZA), 2016)
Studies have shown that the older sibling often chooses to live away from his elderly parents intending to free ride on the care provided by the younger child. In the presented model, we incorporate income effects and depict a different pattern frequently observed in Eastern countries; that is, the older sibling lives near his or her parents and takes care of them in old age. By generalizing the existing model, we show three cases of elderly parents being looked after by (1) the older sibling, (2) the younger sibling, and (3) both siblings, depending on the relative magnitude of the income effect and the strategic incentive for one sibling to free ride on the other. Our study also investigates the effect of changes in relative income on the level of total care received by parents.
Keywords: H41; J17; 330; location choice; income effect; sibling; elderly care arrangement